2009
DOI: 10.1111/j.1463-5224.2009.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral orbital and nasal aspergillosis in a cat

Abstract: A 12-year-old, 4 kg, castrated male Persian cat was referred with a 2-month history of sneezing and bilateral mucopurulent nasal discharge. Rhinoscopically acquired nasal biopsies at this time revealed bilateral lymphoplasmacytic rhinitis. A tapering dose of oral prednisone caused the complete remission of the clinical signs, but 2 months after discontinuation of the therapy, the rhinitis recurred and the OD became exophthalmic. Computed tomography showed a soft tissue mass in both sides of the nasal cavity, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 36 publications
(108 reference statements)
6
62
1
4
Order By: Relevance
“…All cats with SOA had evidence of naso-orbital communication due to lysis of the orbital lamina, identifying direct extension as the likely route of orbital involvement. This is supported by findings on CT, surgery or at post-mortem in other cases, and by the fact that haematogenous spread has not been reported (Barachetti et al, 2009;Barrs et al, 2012;Giordano et al, 2010;Hamilton et al, 2000;Wilkinson et al, 1982). Orbital extension directly from the frontal sinus has been documented in one case (Halenda and Reed, 1997).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…All cats with SOA had evidence of naso-orbital communication due to lysis of the orbital lamina, identifying direct extension as the likely route of orbital involvement. This is supported by findings on CT, surgery or at post-mortem in other cases, and by the fact that haematogenous spread has not been reported (Barachetti et al, 2009;Barrs et al, 2012;Giordano et al, 2010;Hamilton et al, 2000;Wilkinson et al, 1982). Orbital extension directly from the frontal sinus has been documented in one case (Halenda and Reed, 1997).…”
Section: Discussionsupporting
confidence: 62%
“…Feline upper respiratory tract aspergillosis (URTA), first described in 1982, (Wilkinson et al, 1982), is being increasingly reported (Barachetti et al, 2009;Barrs et al, 2012;Declercq et al, 2012;Furrow and Groman, 2009;Giordano et al, 2010;Kano et al, 2008;Kano et al, 2013;Karnik et al, 2009;Smith and Hoffman, 2010). Disease occurs over a wide geographic range, including Australia, the USA, the United Kingdom, mainland Europe, and Japan (Barrs et al, 2012;Barrs et al, 2013;Declercq et al, 2012;Goodall et al, 1984;Kano et al, 2013;Smith and Hoffman, 2010;Tomsa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of feline cases of orbital aspergillosis are on the rise, and the infection is considered an emerging disease [3,5,7,12]. Aspergillus fumigatus has been the most frequently reported etiologic agent of sino-orbital aspergillosis in cats [5].…”
mentioning
confidence: 99%
“…Sometimes they are confronted with breathing problems or problems with clogged tear ducts. It seems that a brachycephalic facial conformation of Persian cats may be an important risk factor for the development of sino-nasal aspergillosis [14] . Furthermore, dental malocclusion and deafness in white Persians are reported commonly in this breed [15] .…”
Section: Introductionmentioning
confidence: 99%